On the Stability of Quadratic Functional Equations in F-Spaces - Xiuzhong Yang (Journal of Function Spaces)
The Hyers-Ulam-Rassias stability of quadratic functional equation f(2x+y)+f(2x-y)=f(x+y)+f(x-y)+6f(x) and orthogonal stability of the Pexiderized quadratic functional equation f(x+y)+f(x-y)=2g(x)+2h(y) in F-spaces are proved.